EVALUATION OF ANTI-INFLAMMATORY ACTIVITY OF AQUEOUS EXTRACT OF MIMOSA PUDICA ON SWISS ALBINO MOUSE - BASUMATARY, HIRINA; BORDOLOI, PALLAVI; DEKA, DIPJYOTI (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: To evaluate the acute anti-inflammatory activity of Aqueous Extract of Mimosa pudica (AEMP) on carrageenan-induced paw edema on Swiss albino mouse and to compare the histopathology findings of control, standard and treated Paws of mouse. Methods: 24 Albino mice (20±2g) were divided into 6 groups. Anti-inflammatory activity using carageenan-induced paw edema method were measured at various intervals on Day 1 followed by histopathological examination of paw. Aspirin was taken as the standard drug, three different doses (100 mg/kg, 200 mg/kg and 400 mg/kg) of AEMP were taken as test drug. Left paw of mouse was considered as control. Statistical analyses were done using Analysis of Variance (ANOVA) followed by Tukey’s multiple comparison tests, p-value<0.05 was considered for significant difference. Results: AEMP showed significant anti-inflammatory activity at all doses (100, 200, 400 mg/kg) when compared to carrageenan-induced group. The study showed that test drug AEMP at the dose of 400 mg/kg produced maximum reduction of paw edema at 4 h. The reduction in paw edema of mice was lower in the 1 h and showed maximum reduction at 4 h. The AEMP significant (p≤0.05) anti-inflammatory activities in a dose-dependent manner to that of the standard drug Aspirin. Conclusion: The study suggests that AEMP has anti-inflammatory property and can be used in the treatment of pain. However, further study is necessary in this regard.